Children and youth as 'sites of resistance' in armed conflict - Shah, Tamanna M. (Sociological studies of children and youth ;, 2024)
During the chaos and devastation of armed conflict, children and youth often emerge as powerful agents of change and resilience. Children and Youth as 'Sites of Resistance' in Armed Conflict, the first of two volumes, is a compelling exploration of their profound roles as active participants, often functioning as sites of resistance within the complex dynamics of warfare. The first volume explores the lived experiences of children and youth in conflict zones, uncovering the different forms of resilience and resistance. Unlike conventional portrayals that confine them solely to victimhood, the chapters address themes such as the intersection of women, children, trauma, and memorialization, as well as the critical examination of human rights and children's rights within the context of armed conflict. They draw from research conducted in conflict areas including Sudan, Israel-Palestine, Ukraine, Kashmir, and Kosovo, which provides a unique insight into the experiences of these children and youth as they navigate the challenges of traumatic events. Highlighting the importance of memorialization in these communities, Children and Youth as 'Sites of Resistance' in Armed Conflict demonstrates this as a means for honouring and commemorating the losses suffered and offers a path toward healing and reconciliation. By shedding light on these intersecting aspects, the scholars amplify the voices of affected children and youth, informing policies, and implementing programs that prioritize their well-being and rights in post-conflict societies. Acknowledging the crucial role of children and youth as catalysts for peace and justice in conflict and post-conflict settings, this is pathbreaking reading for scholars of childhood, youth, peace, and conflict.